PENGEMBANGAN OLAHAN SINGKONG UMKM DF DI KAMPUNG KERIPIK KECAMATAN SELOREJO KABUPATEN BLITAR - Eko Wahyu Budiman; Riska Damayanti (BUANA SAINS, 2023)
The purpose of this study is to identify the marketing mix, identify internal factors and external factors, and identify appropriate alternative strategies. The method used is the 7P marketing mix and SWOT analysis. Based on the results of research and discussion, the most influential internal strength factor is affordable product prices score 0.36, in terms of promotion weaknesses with a score of 0.08. The influential external factor in terms of opportunity is the development of social media score of 0.36. In the threats, the most influential competitor's human resources are superior. The competitors' distribution channels are wide score 0.14. SWOT analysis is in quadrant I supports an aggressive growth policy and growth-oriented strategy, by utilizing the company's strengths to obtain as many opportunities as possible. Alternative strategies which implemented are working with related parties (gift shops), increasing production quantity, and utilizing social media in promotions.